Literacy, orality and recontextualization in the parliament of the Republic of South Africa : an ethnographic study - Siebörger, Ian (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2012)
In parliaments, the tasks of drafting legislation and conducting oversight are accomplished by means of complex chains of spoken, written and multimodal texts. In these genre chains, information is recontextualized from one text to another before being debated in sittings of the houses of parliament. This study employs the point of view afforded by linguistic ethnography to investigate critically the ways in which meanings are recontextualized in one section of such a genre chain, namely the process by which committees of South Africa's National Assembly oversee the budgets of government departments and state-owned entities. It does this to identify possible sources of communication difficulties in this process and suggest ways in which these can be minimized. In so doing, it develops a theoretical model of the discursive effects of recontextualization informed by Latour's (1987) notion of black-boxing as well as Maton's (2011) Legitimation Code Theory. This model uses Interactional Sociolinguistics and elements of Systemic Functional Linguistics, including APPRAISAL and Transitivity as tools to describe the realization of these effects in language. This study finds that ideational and interpersonal meanings are condensed and decondensed at particular points in the genre chain in ways that lead to some MPs' voices being recontextualized more accurately than others'. It also shows that common sources of communication difficulties in the committee process include differences in political background and understandings of committee procedure and participant roles. It recommends that representatives of departments and entities reporting to the committees should receive a fuller prebriefing on their roles; that MPs should receive training on asking clear, focused questions; and that the role of committee secretaries as procedural advisors should be strengthened.
Keywords: South Africa. Parliament (1994- ) -- Language; Bill drafting -- South Africa; South Africa -- Languages -- Political aspects; Sociolinguistics -- South Africa; Language and languages -- Variation; Linguistic analysis (Linguistics); Functionalism (Linguistics); Systemic grammar